Nutrient-Based Appetite Regulation - Jose M. Moris; Corrinn Heinold; Alexandra Blades; Yunsuk Koh (Journal of Obesity & Metabolic Syndrome, 2022)
Regulation of appetite is dependent on crosstalk between the gut and the brain, which is a pathway described as the gut-brain axis (GBA). Three primary appetite-regulating hormones that are secreted in the gut as a response to eating a meal are glucagon-like peptide 1 (GLP-1), cholecystokinin (CCK), and peptide YY (PYY). When these hormones are secreted, the GBA responds to reduce appetite. However, secretion of these hormones and the response of the GBA can vary depending on the types of nutrients consumed. This narrative review describes how the gut secretes GLP-1, CCK, and PYY in response to proteins, carbohydrates, and fats. In addition, the GBA response based on the quality of the meal is described in the context of which meal types produce greater appetite suppression. Last, the beneficiary role of exercise as a mediator of appetite regulation is highlighted.